Customer Experience as A Mediation of Omnichannel Retailers of Wardah Beauty Products on Repurchase Intentions - Romindo M. Pasaribu; Herry D.S. Pasaribu (International Journal of Marketing & Human Resource Research, 2021)
Current technological developments require companies to develop their business with various purchasing or shopping channels. The business model that is currently trending is the omnichannel model. Omnichannel is a business model which in its operation and service is integrated in all sales channels owned by the company in one overall system. Omnichannel combines all store marketing channels both online and offline which can make it easier for customers to find information, process, and make decisions in making product purchases. The purpose of this study was to analyze customer experience as a mediating variable between the quality of the integration channel consisting of Service Configuration Quality (SCQ) and Interaction Integrated (II) on repurchase intentions on Wardah beauty products as a local brand in Indonesia. The object of this research is a beauty product with the brand Wardah and the research was conducted in the city of Medan. The data analysis method was carried out using SmartPLS. The result of this study is that service configuration quality has no positive and significant effect on the repurchase intention variable. Integrated interactions have a positive and insignificant effect on the repurchase intention variable. Service configuration quality and integrated interactions have a positive and significant effect on customer experience. Customer experience has a positive and significant effect on repurchase intention. Service quality configuration and integrated interactions are not positive and significant effect on repurchase intention through the customer experience as mediation. In this study, the customer experience was not able to mediate between service configuration quality and integrated interactions on repurchase intention.